Bag Valve Mask Ventilation Versus Controlled Ventilation for Minor Pediatric Surgery. - Panta, Sunita; KC, Nagendra Bahadur (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Paediatric anaesthesia deals with Examination under anaesthesia to complicated surgical interventions. Most of the minor surgeries can be performed with Bag Valve Mask Ventilation which avoids complications of endotracheal intubation. Methods: A retrospective randomized control study was undertaken in 654 paediatric surgeries performed at Shree Birendra Hospital, Chhauni (April 2005-March 2010). The children underwent minor general, Ear nose throat and orthopaedic surgery to compare spontaneous Bag Valve Mask ventilation in 503 patients (BVM Group) and controlled ventilation in 151 patients (CV Group). The BVM group was done under spontaneous mask ventilation and CV group under endotracheal intubation. Anaesthesia was induced and maintained with oxygen and halothane, using a Mapleson F system with spontaneous ventilation and a Rendell-Baker face mask. The duration of anaesthesia was less than one hour. Results: In this study we noted the complications like trauma to face and lips, dental trauma, laryngospasm, perforation of tracheaor esophagus, pulmonary aspiration of gastric contents or foreign bodies and post extubation complications. Conclusions: It is concluded that the need of controlled ventilation with endotracheal tube is limited to only a few procedures and many of the paediatric surgeries can be performed with spontaneous mask ventilation. Therefore anaesthesia with oxygen and halothane with spontaneous mask ventilation is a satisfactory method for minor procedures in children. Medical Journal of Shree Birendra Hospital; Jan-June 2012/vol.11/Issue1/17-20 DOI: http://dx.doi.org/10.3126/mjsbh.v11i1.7761